Detection of Salmonella spp. from zoo animals in Iran, determination of serovars, antibiotic susceptibility and genotyping by RAPD-PCR - FASAEI, B. N.; TAMAI, I. A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Salmonellosis is an important food-borne bacterial zoonotic disease that affects both people and animals. Contamination sources include direct or indirect animal contact. We determined and measured the risk of Salmonella infection from zoo animal to human contact by isolation of Salmonella serovars from zoo animals kept at Karaj zoo park, Iran. Salmonella was isolated from 21 (20%) of the 104 anal swap samples. From the 21 collected samples 4, 7 and 10 were originated from birds, mammals and reptiles, respectively. Serotyping detected nine different serotypes including Enteritidis (n=4), Seftenberg (n=1), Typhimurium (n=4), Virchow (3), Berkeley (n=1), Kingabwa (n=2), Newport (n=2), Marina (n=2) and Havana (n=1). All the isolates except one (serovar Marina subspecies Hautenae IV) were belonged to Salmonella enterica subspecies enterica I. Salmonella enterica serotypes Typhimurium and Enteritidis were the most commonly detected serotypes. All the isolates tested, were resistant to one or more antibiotics and five isolates including the monkeys’ and long-eared owls’ isolates were multiresistant. RAPD profiles of each isolate produced with two different primers were identical. These finding shows highly contamination of zoo animals from Salmonella especially from the multiresistant isolates. All of the animals in the zoo, pet owners, veterinarians, zookeepers and visitors are at high risk of salmonellosis with reptiles being the most important source of infection.